PERAN GURU FIQIH DALAM PEMBENTUKAN AKHLAK PESERTA DIDIK - Naziha (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to comprehensively examine the role of fiqh teachers in shaping students’ moral character within the context of Islamic education. Fiqh teachers do not merely function as transmitters of Islamic legal knowledge, but also serve as mentors, role models, motivators, and evaluators in the process of internalizing moral values. This research employs a qualitative approach using a literature study method, drawing on books, academic journals, and other relevant sources. The findings indicate that the role of fiqh teachers is highly significant in shaping students’ character, particularly through exemplary behavior (uswah hasanah), habituation of good conduct, provision of advice, and the integration of moral values into the learning process. Furthermore, the success of moral development is influenced by supporting factors such as a religious school environment, parental involvement, and a well-structured curriculum. On the other hand, inhibiting factors include negative influences from social media and a lack of supervision within the family environment. In conclusion, fiqh teachers play a strategic role in developing a generation that is not only intellectually competent but also possesses noble character. Therefore, synergy among teachers, schools, and parents is essential in creating a conducive educational environment for character building.